Histop: alternative patch for rapid arrest of bleeding from leaves of hibiscus rosa-sinensis / Nur Dayana Hassan Cheong ... [et al.] - Hassan Cheong, Nur Dayana; Jamaludin, Nuraini Nafisah; Ahmad Shapi’I, Hanisah; Mohd Zan, Yasmin Suraya; Elias, Iadah; Rambely, Azlin Sham; Mohamed, Emida (2020)
Uncontrolled haemorrhage leads to over 30% of trauma deaths worldwide and more than half of those are due to delayed medical attention. HiStop is prepared from the extract of the leaves of Hibiscus rosasinensis or ‘bunga raya’ which has been found to harbour procoagulant activity. Besides accelerating the clotting process, the leaves extract of H.rosa-sinensis has also been reported to possess antimicrobial activity. Hence, when applied to bleeding wounds, HiStop seals the wound, stops bleeding and also act as a barrier to bacterial infections. Preparation of HiStop started with the leaves of H.rosa-sinensis being blended with distilled water. Decoction method was then used to concentrate the crude extract. Four percentages of aqueous extract were prepared at 100.0%, 50.0%, 25.0% and 12.5% using normal saline. Then, procoagulant activity was evaluated in vitro by using activated partial thromboplastin time (aPTT) and prothrombin time (PT) tests in triplicates. The result revealed a procoagulant trend with the coagulation time decreasing as the percentages increased. All percentages of aqueous extracts showed very highly significant effect on both aPTT and PT tests with their p value obtained were equal to 0.000. Hence, the aqueous extract from H.rosa-sinensis leaves has the potential to be used as a natural haemostatic for treatment of minor bleeding. The extract was then lyophilized and dispensed in ‘tea bag’ like sachets to be applied directly to wound. It is easy to use, flexible and portable for external usage and acts as a temporary control of bleeding wounds, intended for emergency use.